Напрями вдосконалення адміністративного законодавства, яке регулює взаємодію між органами публічного адміністрування та суб’єктами підприємницької діяльності - Іняхін, В. Є.; Iniakhin, V. Ye. (Наше право. - 2020. - № 3. - С. 237-241, 2020)
Запропоновано авторське бачення перспективних напрямів удосконалення адміністративного законодавства, яке регулює взаємодію між органами публічного адміністрування та суб’єктами підприємницької діяльності. Акцентовано увагу, що вдосконалення відповідного законодавства має здійснюватись у двох напрямках: нормативно-правовому та організаційно-управлінському.

It is noted that while carrying out reforms in the field of public administration, as well as in the field of economic (entrepreneurial) activity, the legislator constantly focuses on the fact that achieving the desired goal is actually impossible without proper interaction between state authorities and business. After all, the financial and economic stability of the state and society as a whole directly depends on their cooperation. However, as a shortcoming of all the legal acts analyzed in the article, it was noted that the legislator actually left out of his attention the issue of legal and organizational support for the interaction of public administration bodies and business entities. It has been established that neither at the legislative nor at the scientific level has a single approach been developed regarding promising directions for the improvement of administrative legislation, which regulates the interaction between public administration bodies and subjects of entrepreneurial activity. The following are among the promising areas of improvement of administrative legislation, which regulates the interaction between public administration bodies and business entities: 1) normative and legal, within which it is considered necessary to develop and adopt: a) “Concepts for the development of public administration bodies”; b) “Concepts for improving the interaction of public administration bodies and business in Ukraine”; c) “Procedure of interaction between public administration bodies and business entities”; 2) organizational and management direction, which provides for: a) simplification of procedures and reduction of bureaucracy. As can be seen, the optimization of documentation requirements and the minimization of bureaucratic obstacles will contribute to faster and more effective interaction between entrepreneurs and government bodies; b) development and implementation of electronic platforms for submitting documents, requests and reporting; c) establishment of clear norms and procedures for the protection of the rights of business entities, including mechanisms for appealing the decisions of state bodies; d) ensuring public access to information about the activities of state bodies, their decisions and procedures; e) implementing mechanisms of mediation and alternative settlement of disputes; e) identification of risk areas and directing resources to control and regulation exactly where it is most needed.

Предложено авторское видение перспективных направлений усовершенствования административного законодательства, регулирующего взаимодействие между органами публичного администрирования и субъектами предпринимательской деятельности. Акцентировано внимание, что усовершенствование соответствующего законодательства должно осуществляться в двух направлениях: нормативно-правовом и организационно-управленческом.
Keywords: адміністративне законодавство; взаємодія; органи публічного адміністрування; суб’єкти підприємницької діяльності; administrative legislation; interaction; public administration bodies; business entities; административное законодательство; взаимодействие; органы публичного администрирования; субъекты предпринимательской деятельности